Islamic Cooperatives: A Review of the Theory of Truth in Islamic Economic Philosophy - Nasrulloh, Agus Ahmad; Syarif, Nurrohman; Ridwan, Ahmad Hasan (Universitas Siliwangi, 2025)
Introduction to The Problem: Islamic cooperatives have an important role in the national economy, especially for business actors in the Micro, Small and Medium Enterprises sector. However, currently the function and role of this financial institution cannot run optimally because it is faced with problems originating from internal and external Islamic cooperatives. This is allegedly contrary to the theory of truth in Islamic philosophy.Purpose/Objective Study: This research aims to examine and analyse the role and function of Islamic cooperatives in terms of the theory of truth in Islamic philosophy.Design/Methodology/Approach: This research is a type of qualitative research in the form of library research which is qualitative in nature.Findings: Islamic cooperatives have a strategic role in supporting the development of MSMEs, with approaches that are aligned with theories of truth, such as correspondence theory that emphasises conformity with reality, coherence theory that prioritises consistency in value systems, pragmatism theory that focuses on practical benefits, and performative theory that assesses the effectiveness of actions in achieving goals. The low level of Islamic financial literacy among MSME players, which often hinders their understanding of the benefits of Islamic financing. In addition, intense business competition in the market is also a significant obstacle that requires a special strategy. By overcoming these obstacles, Islamic cooperatives can further strengthen their function as a key pillar in supporting the sustainable growth of MSMEs.Paper Type: Research Article